THE INFLUENCE OF MEDIA USE ANIMATION TO STUDENT LEARNING OUTCOMES IN A HYDRAULICS SUBJECT - Emha Komar Priatna; Sri Murwantini (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2018)
In general, the teaching and learning process in the classroom are using conventional media, in the form of images, as well as the teacher explaining by using lecture method is difficult for students to be understood regarding the engineering courses such as air compressor subject. By using conventional media on subjects Hydraulic System Maintenance and Air Compressors, those subjects are at the average score of students measuring the cognitive condition at about still below KKM 70 or 68. Media animation is one of the options of learning media that can be used to overcome these problems, so that is expected to increase student scores from previous score. The purpose of this study was to know the influence of media use like animation to the learning outcomes of students on the hydraulics subject. This research used experimental research applying True Type Design Posttest - Only Control Design. This research population is all students of class X TSM and TKR at academic year 2016/2017 in SMK Karsa Mulya Palangkaraya. Sample of research is a class X TKR at around 40 students as a class experiment and X TSM A at total of 36 students as the control class. Both samples were taught differently, classroom learning experiment with animation media teaching and control class treatment using the conventional learning media. In this study, it will be assessed there are 3 domains. The division of the realm is cognitive learning outcomes by 50%, 20% for affective aspect and psychomotor at 30%. Instrument on cognitive tests is a matter of learning outcomes, then the affective aspect and psychomotor were using observation sheet. Based on the research and analysis of data, it can be concluded that the results of data normality test students learning outcomes in experimental class and control class have performed the normal distribution and homogeneous term. The hypothesis test using ttest was obtained price for thitung> ttable 6.9> 2.032. Then H0 is rejected followed H1 accepted. This meant that there is the effect of using animation media to student learning outcomes in a hydraulics course subject.